Cell surface nucleolin as active bait for nanomedicine in cancer therapy: a promising option. (17th May 2021) - Ferrara, Benedetta; Belbekhouche, Sabrina; Habert, Damien; Houppe, Claire; Vallée, Benoit; Bourgoin-Voillard, Sandrine; Cohen, José L; Cascone, Ilaria; Courty, José
Abstract: Conventional chemotherapy used against cancer is mostly limited due to their non-targeted nature, affecting normal tissue and causing undesirable toxic effects to the affected tissue. With the aim of improving these treatments both therapeutically and in terms of their safety, numerous studies are currently being carried out using nanoparticles (NPs) as a vector combining tumor targeting and carrying therapeutic tools. In this context, it appears that nucleolin, a molecule over-expressed on the surface of tumor cells, is an interesting therapeutic target. Several ligands, antagonists of nucleolin of various origins, such as AS1411, the F3 peptide and the multivalent pseudopeptide N6L have been developed and studied as therapeutic tools against cancer. Over the last ten years or so, numerous studies have been published demonstrating that these antagonists can be used as tumor targeting agents with NPs from various origins. Focusing on nucleolin ligands, the aim of this article is to review the literature recently published or under experimentation in our research team to evaluate the efficacy and future development of these tools as anti-tumor agents.